Study of Incidence of Hypoglycemia after Diabetes Remission Policy in Thailand - หาญบรรเจิด กฤษฏา; พันธ์มุง ณัฐิวรรณ (Journal of Health Science of Thailand, 2026)
Hypoglycemia is a common and serious complication in diabetic patients undergoing intensive glycemic control. Inappropriate dose reduction or discontinuation of medications relative to lifestyle modifications during diabetes remission management can lead to hypoglycemic events. This study was conducted among diabetic patients at Ban Ta Khun Hospital who were enrolled in the diabetes remission program. Secondary data were collected from the hospital database for all patients in the remission clinic from January 2019 to October 2024, totaling 172 participants. A retrospective cohort study was employed to determine the incidence of hypoglycemia and identify associated risk factors. The results showed an incidence of hypoglycemia in 14 patients (8.1%), totaling 22 events (12.8 events per 100 person-years). Univariate analysis revealed that obesity (BMI ≥30.0 kg/m2) and the use of insulin and/or insulin secretagogues during the service period were significantly associated with an increased risk of hypoglycemia, with risk ratios (RR) of 1.28 (95%CI 1.01 – 1.64; p<0.05) and 2.52 (95%CI 1.13 – 7.19; p<0.05), respectively. Furthermore, multivariate logistic regression analysis confirmed that obesity and the use of diabetic medications were significant independent risk factors, with adjusted odds ratios (aOR) of 6.60 (95%CI 1.49 – 29.16; p<0.05) and 30.71 (95%CI 5.40 – 174.72; p<0.05), respectively. The incidence of hypoglycemia among patients in the diabetes remission program is relatively low compared to conventional intensive glycemic control. Nevertheless, it is recommended to strictly follow de-prescribing guidelines for the medication groups, exercise caution regarding overly restrictive diets in obese patients, and consider appropriate physical activity levels particularly for those still in the workforce to prevent hypoglycemic episodes.